A new species of the Hyalella ‘azteca’ complex (Crustacea: Amphipoda: Hyalellidae) from Florida - Drumm, David T.; Knight-Gray, Julianne (Zootaxa, 2019)
Examination of material from the Wakulla River in north-western Florida revealed the presence of a new species of the amphipod genus Hyalella. It appears to be most closely related to H. azteca (Saussure) sens. strict., but can be distinguished by the nature of maxilla 1 and the telson. The setation of uropod 3 has been given systematic importance for this genus, but we show in the present paper that this character exhibits high intraspecific variation, even within the same individual. This is the first formally described species of Hyalella from Florida.